Dimensions of the work of the nurse in the hospital setting - Presotto, Giovanna Valim; Ferreira, Maria Beatriz Guimarães; Contim, Divanice; Simões, Ana Lúcia de Assis (Rev Rene, 2014)
his research aimed at understanding the perception of nurses concerning the dimensions of work in the daily activities of a university hospital. It is a descriptive, exploratory and qualitative study made with 19 nurses working in a Federal University Hospital in Minas Gerais, Brazil. Data were collected in August and September 2010, through interviews, and submitted to content analysis. The results showed four distinct dimensions: aspects related to human care, to the management of care and service, to the permanent education and to the need to produce and make use of the results of the research. It is concluded that nurses recognize the extent of their work and their interfaces in the hospital setting. The study of aspects related to the work process can contribute to the construction of the identity of the nurse and the strengthening of the profession.